A scientific companion to Robert Frost - Smith, Virginia F., 1961- (Liverpool scholarship online., 2018)
"A Scientific Companion to Robert Frost represents the first systematic attempt to document all of the references to science and natural history in Frost's poetry. The book, which is organized chronologically, uses accessible language and includes illustrations and appendices that should make it a valuable resource for teachers and scholars"--